PENYEMBUHAN DAN PERBAIKAN MORAL WANITA PENGHIBUR - Jodi Adam; J.M. Joko Priyono Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Globalization has brought many significant changes and impacts to the world, both positive and negative. On the one hand, globalization has brought technological advances and information that enable access to faster and easier information and communication, as well as increasing international trade and foreign investments that can drive economic growth. On the other hand, globalization is also potentially exacerbating the social and economic disparity between strong and weak countries, as well as strengthening the influence of multinational forces and global organizations to make decisions that can affect human life. And free association is one of the effects of globalization itself. Promiscuity is a social phenomenon with such a variety of forms as murder, alcoholic beverages, smoking, brawling, and sexual promiscuity. Casual sex is one form of free association and the effects of casual sex: premature marriage, abortion, and HIV. HIV is a very lethal impact. The spread of HIV is free of the three factors: female entertainers, drug use, and poor dipper. Female entertainers are a form of sexual promiscuity. On the other hand, a lack of empathy for society leads to mental, psychological and biological problems for prostitutes. In this regard, empathy for female entertainers also plays a key role in promoting more inclusive and friendly social changes for individuals involved in tuna. In building empathy for female comforters, society needs to treat them with respect, tolerance, and understanding. Thus, it is hoped that a more inclusive and friendly social environment will be created for all individuals in society, through architecture. The project employs methods of juhani pallasmaa's theory "an architecture of seven sense" and "the eyes of the skin: architecture and sense" and through data collecting from BPS's internal media, e.book, surveys, interviews and semisters, and analysis of the needs of the surrounding communities. It is to be expected that empathy remains and remains until recently, with a design consistent with the characteristics of empathy. Keywords:  Free association, Sex workers, Rehabilitation Abstrak Globalisasi telah membawa banyak perubahan dan dampak signifikan bagi dunia, baik positif maupun negatif. Di satu sisi, globalisasi telah membawa kemajuan teknologi dan informasi yang memungkinkan akses informasi dan komunikasi yang lebih cepat dan mudah, serta meningkatkan perdagangan internasional dan investasi asing yang dapat mendorong pertumbuhan ekonomi. Di sisi lain, globalisasi juga berpotensi memperburuk kesenjangan sosial dan ekonomi antara negara-negara yang kuat dan lemah, serta memperkuat pengaruh kekuatan multinasional dan organisasi global dalam mengambil keputusan yang dapat mempengaruhi kehidupan manusia. Dan pergaulan bebas salah satu dampak dari globalisasi itu sendiri. Pergaulan bebas adalah fenomena sosial memiliki beragam bentuk seperti : pembunuhan, minuman berakohol, merokok, tawuran, dan sex bebas. Sex bebas salah satu bentuk pergaulan bebas dan dampak dari sex bebas adalah: pernikahan dini, aborsi, dan hiv. Hiv adalah dampak yang sangat mematikan. Penyebaran hiv di sebebkan dari tiga faktor yaitu : tuna Susila, penggunaan narkotika suntik, dan pendudduk miskin. Tuna Susila salah satu bentuk korban dari sex bebas. Di sisi lain kurangnya empati terhadap masyarakat sehingga menimbulkan masalah mental, psikologis dan biologis pada tuna Susila. Dalam hal ini, empati terhadap tuna susila juga berperan penting dalam mempromosikan perubahan sosial yang lebih inklusif dan ramah bagi individu yang terlibat dalam tuna susila. Dalam membangun empati terhadap tuna susila, masyarakat perlu memperlakukan mereka dengan penuh rasa hormat, toleransi, dan pengertian. Dengan begitu, diharapkan akan tercipta lingkungan sosial yang lebih inklusif dan ramah bagi semua individu dalam masyarakat, melalui arsitektur. Proyek ini menggunakan metode dari teori Juhani Pallasmaa “An architecture of seven sense” dan “The eyes of the skin: architecture and sense” dan melalui pengumpulan data dari BPS DKI Jakarta, jurnal ilmiah, e-book, survei, wawancara dan kuisioner, serta analisis kebutuhan masyarakat sekitar. Dengan ini diharapkan rasa empati tetap terasa dan terjaga sampai kapanpun, dengan desain sesuai dengan karakteristik empati.